Revolutionizing Victim Identification: Cutting-Edge Dental Implant Recognition in Forensic Odontology- A Review - Sangeetha Ramu (International Journal of Medical Toxicology and Legal Medicine, 2024)
Disaster victim identification, particularly in mass casualty incidents like air, naval, railway, motorway accident, flooding, earthquake, relies significantly on dental identification. The widespread integration of dental implants in dentistry has transformed them into a valuable source of antemortem data. This research review paper delves into recent advancements in forensic odontology’s dental implant identification techniques. The study explores the application of implant recognition software, radiographic identification of dental implants, and batch number assessment, all aimed at supporting forensic odontologists in the intricate process of victim identification. Additionally, the research investigates the potential of these techniques to unveil information regarding the victim’s geographical location and socioeconomic status. The findings demonstrate a substantial enhancement in the efficiency and accuracy of dental implant identification through the integration of implant recognition software. Radiographic recognition methods prove effective in visualizing dental implants, even under challenging conditions. Moreover, batch number assessment emerges as a valuable tool for discerning the origin of the implant. In conclusion, dental implants have become indispensable elements of an individual’s antemortem records, with recent technological innovations significantly enhancing their role in forensic odontology. The amalgamation of implant recognition software, radiographic identification and batch number assessment, not only streamlines victim identification but also provides nuanced insights into the victim’s socioeconomic background and origin. This multifaceted understanding proves critical, particularly in complex scenarios such as incineration.